Maternal postpartum feeding anxiety was associated with infant feeding practices: results from the mother-infant cohort study of China - Jing Sun; Yimin Zhu; Yongjin Li; Niuniu Li; Tan Liu; Xiao Su; Zhiyong Dai; Yanchun Zhang; Lina Pan; Wei Jiang; Wenli Zhu (BMC, 2020)
Abstract Background Maternal feeding anxiety (FA) was prevalent during puerperium and might affect infant feeding practices. This study was aimed to investigate the FA status in Chinese postpartum women and its relationship with infant feeding practices (FPs). Methods Participants were from the Mother-Infant Cohort Study of China, in which the dietary and feeding practices, physical and psychiatric health for both mothers and infants were followed up from childbirth to next 2 years. In this study the maternal feeding anxiety (FA) status at 0-3 months postpartum was assessed by Li's Self-rating Feeding Anxiety Scale (SFAS). Infant feeding practices (FPs) at 0-3 months, including breastfeeding-related behaviors, responsive feeding and infant food refusal were investigated by self-designed questionnaire. Results In total 456 mothers the average feeding anxiety scores (FAS) was 41.02 ± 8.02 (mean ± SD), and maternal FA prevalence were 61.4% (FAS>38) with severe FA being 8.6% (FAS>52) at 0-3 months postpartum. The FAS was related with infant FPs, and lower maternal FAS was significantly related with infant colostrum feeding (40.86 ± 8.02 vs 44.74 ± 11.33, P < 0.05), but higher FAS was related with bottle feeding (41.95 ± 8.28 vs 39.69 ± 7.92, P < 0.05). The mothers with severe feeding anxiety (FAS > 53) were more likely to feed infants with bottle (ORs, 95%CI: 2.41, 1.11 ~ 5.19). There were not significant association between FAS and exclusive breastfeeding and responsive feeding practices (P > 0.05). The higher FAS was associated with infant food refusal behaviors, the maternal scores whose infant "never", "rarely", "sometimes" and "often" spat out food when feeding were 39.86 ± 8.02, 41.47 ± 8.18, 41.36 ± 7.44 and 42.14 ± 12.03 increasingly (P > 0.05), and the FA prevalence was significantly different among groups (P < 0.05). The infants whose mother was identified as feeding anxiety were more likely to refuse opening the mouth when feeding (P < 0.05). Multivariate analysis indicated maternal FAS was positively related to infant bottle feeding (βi = 2.487, P < 0.05) and outdoor sunshine exposure practice (βi = 1.787, P < 0.05), and negatively related to household income level (βi = − 0.118, P < 0.05). Conclusions Maternal postpartum feeding anxiety was associated with some infant feeding practices, including bottle feeding and infant food refusal behaviors.